PMO-190 Investigating the prevalence and cause of iron deficiency in a faecal occult blood positive, colonoscopy negative patients from the UK Colorectal Cancer Screening Programme. (28th May 2012) - Murino, A; Despott, E J; Postgate, A; O'Rourke, A; Fraser, C
Abstract : Introduction: Faecal occult blood test (FOBT) is a simple test, which detects small amounts of blood released from the gastrointestinal tract. Recently it has been adopted as discriminator test for the BCSP in the UK. A colonoscopy is strongly recommended when FOBT results test positive. At present there are no plans for further investigation of the source of blood loss in patients who have had a negative colonoscopy. The aim of this study was to identify the proportion of UK colorectal cancer screening patients with a positive FOBT and negative colonoscopy affected by iron deficiency (ID) or iron deficiency anaemia (IDA) and then to detect any source of blood loss in the upper GI tract or small bowel. Methods: 100 patients with a positive FOBT referred for a BCSP were prospectively enrolled in the study between January 2008 and September 2010. A full blood count and ferritin were acquired after a negative colonoscopy. Patients with identified ID or IDA were invited to have an oesophagogastroduodenoscopy (OGD) and small bowel capsule endoscopy (SBCE). Results: 100 patients (male: 70, female: 30) with a positive FOBT referred to our tertiary centre had a negative colonoscopy. 19 patients were excluded due to vegetarianism. Of the remaining 81 patients, 1 had ID and 3 had IDA (4.9%) and therefore underwent OGD and SBCE. In 2/4 patients both procedures were normal. Three superficial gastric antral ulcers and a few gastric erosions were diagnosed respectively in the other two patients (2.4%), while their SBCEs were negative. Both patients had a history of aspirin or NSAID usage. Conclusion: In this cohort of FOBT positive and colonoscopy negative patients from the UK BCSP, we found that the prevalence of ID and IDA was 4.9%. Of these four patients only 2 (2.4%) had positive findings when further investigated, but these could be explained by medication. If these patients are excluded from the analysis then OGD and SBCE post negative colonoscopy in FOBT positive patients cannot be recommended. Competing interests: None declared.